Становлення анекдоту в системі фольклорних жанрів (на прикладі мотиву "била жінка мужика") - Кімакович, І. (Народна творчість та етнографія, 2006)
The article studies the evolution of “wife beats her husband” motive in ritual and secular texts belonging to different epochs. The transformation of archaic notions connected to the concept of laugh is exposed.